Exploration of Village Community Figures' Health Beliefs Towards Covid-19 - Maina Afrida; Aslam Nur; Radhiah Zakaria; Asnawi Abdullah; Meutia Zahara (GLOBAL HEALTH SCIENCE GROUP, 2025)
COVID-19 is a global pandemic that threatens everyone's health. The increase in confirmed COVID-19 cases continues to occur, including in Aceh Besar Regency. Public health intervention efforts have proven effective in reducing the incidence of COVID-19 and community leaders can be involved in these public health intervention efforts. Public health interventions are expected to cause changes in health behavior, but these behavioral changes require health beliefs. This study is a qualitative study with an exploratory approach to determine the beliefs of community leaders towards COVID-19. The number of informants in this study was 8 community leaders who were selected by purposive sampling. Data collection was carried out by conducting in-depth interviews. Data analysis in this study was carried out before entering the field, while in the field and after finishing in the field. The results of the interviews showed that the health beliefs of community leaders towards COVID-19 were influenced by the sources of information obtained, beliefs about COVID-19, the attitudes of community leaders towards people around them who were infected with COVID-19 and knowledge about the dangerous impacts of COVID-19. Good knowledge will increase the trust of community leaders and improve the attitudes of community leaders to participate in the COVID-19 vaccination which is one of the preventions of COVID-19. Community leaders are also involved in helping health workers provide information about efforts to prevent and handle COVID-19. It is hoped that community leaders will play an active role in efforts to prevent and handle COVID-19 by increasing knowledge and attitudes about COVID-19 which can be obtained through online and print information media. In addition, community leaders are expected to work together with health workers in preventing COVID-19.